Strategi Pembelajaran Berdiferensi untuk Mengatasi Hambatan Pemahaman terhadap Alur dan Tokoh dalam Teks Fabel pada Siswa Kelas IV Sekolah Dasar: Penelitian - Hesti; Musiman; Maretha, Carla; Idawati; Tussolekha, Rohmah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe differentiated learning strategies in overcoming obstacles in understanding the plot and characters in fable story texts for the fourth-grade of SDIT Smart Insani students. Students face problems in identifying the sequence of events and in understanding the characters in the fable story text. Differentiated learning strategies are applied by referring to the conditions of each student. The differentiation is implemented in; 1) content, 2) process, 3) and product. This study used a descriptive qualitative approach. Data was collected through observation, interviews, and documentation. The results of this study indicate that the use of differentiated learning strategies has proven effective in improving elementary school students' understanding of the plot and characters in fable story texts. Students with low comprehension abilities are helped by collaborative activities and visual media, while students who have higher comprehension abilities are given challenges towards deeper learning in understanding the meaning of the story.